Volume 4: Heat Transfer, Parts a and B 2010
DOI: 10.1115/gt2010-22774
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Film Cooling Effectiveness With New Shaped Holes

Abstract: Gas Turbine Engines operate at temperatures higher than current material temperature limits. This necessitates cooling the metal through internal or external means and/ or protecting the metal with coatings that have higher material limits. Film cooling is one of the major technologies allowing today’s gas turbines to operate at extremely high turbine inlet temperatures, consequently higher power density, and extend the cooled components life. Film cooling is a technique where a coolant is blown over the surfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…A review of shaped hole geometries found in the literature identified 130 different hole designs. Geometries included conical, laidback, and fanshaped holes [2][3][4][5][6], and many novel designs: bean-shaped [7], cusp-shaped [8], crescent-shaped [9], cratered [10], "Console" [11], double-jet [12], Nekomimi [13], transonic wall jet [14], waist-shaped [15], arrowhead-shaped [16], and anti-vortex holes [17]. The review included not only flat-plate studies, but also endwall, airfoil, and test coupon studies that featured shaped holes [18][19][20].…”
Section: Review Of Relevant Literaturementioning
confidence: 99%
“…A review of shaped hole geometries found in the literature identified 130 different hole designs. Geometries included conical, laidback, and fanshaped holes [2][3][4][5][6], and many novel designs: bean-shaped [7], cusp-shaped [8], crescent-shaped [9], cratered [10], "Console" [11], double-jet [12], Nekomimi [13], transonic wall jet [14], waist-shaped [15], arrowhead-shaped [16], and anti-vortex holes [17]. The review included not only flat-plate studies, but also endwall, airfoil, and test coupon studies that featured shaped holes [18][19][20].…”
Section: Review Of Relevant Literaturementioning
confidence: 99%
“…They found that high mainstream turbulence intensity only decreased the film cooling effectiveness under small blowing ratios. In recent years, some new shaped film hole configurations have been introduced, such as converging slot hole [23], waist-shape slot hole [24], dumbbell and bean shaped holes [25], NEKOMIMI film hole [26], and novel sister shaped hole [27]. But the majority of these ideas prove to be difficult to manufacture to make their way into production.…”
Section: Introductionmentioning
confidence: 98%
“…Results from Yao et al [13,14] demonstrate that the CONSOLE produces better effectiveness and cuts down the aerodynamic loss compared with the cylindrical hole. Other investigators [15][16][17] also came up with some innovative cooling geometries which were verified to produce better cooling performance than fan-shaped holes.…”
Section: Introductionmentioning
confidence: 98%